2003
DOI: 10.3184/030823403103174434
|View full text |Cite
|
Sign up to set email alerts
|

Nickel and Palladium Catalysed Reaction of Triethyl Phosphite with Aryl Halides under Microwave Irradiation

Abstract: Diethyl aryl phosphonates are efficiently and rapidly obtained from halides and triethyl phosphite without solvent. The reaction was catalysed by NiCl2 or PdCl2 (10%) under focussed microwave radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Later on, the Arbuzov reaction was also accomplished under solventless microwave (MW) conditions. Although the arylphosphonates were prepared in 62–98% yields, the procedure is not reproducible as a domestic MW oven was applied and the temperatures were not detected and given . Others and we found that MW may be an invaluable tool in organophosphorus chemistry.…”
Section: Introductionmentioning
confidence: 93%
“…Later on, the Arbuzov reaction was also accomplished under solventless microwave (MW) conditions. Although the arylphosphonates were prepared in 62–98% yields, the procedure is not reproducible as a domestic MW oven was applied and the temperatures were not detected and given . Others and we found that MW may be an invaluable tool in organophosphorus chemistry.…”
Section: Introductionmentioning
confidence: 93%
“…Thermolysis in acetic anhydride led to functionalisation of the proximate benzylic site generating the acetate ester, 4 . Palladium catalysis of C−P bond formation using P(OEt) 3 , followed by selective base hydrolysis of the carboxylate ester, gave the primary alcohol, 6 , from which the mesylate, 7 , was prepared under standard conditions.…”
Section: Resultsmentioning
confidence: 99%
“…For alkyl substrates the reaction works fine even under solvent‐free conditions and it is usually complete in a few hours, whereas for aryl derivatives 1,3‐diisopropylbenzene is normally used and longer times (16–24 h) are needed. Microwave (MW) heating under solvent‐free conditions has recently been exploited to speed up the reaction with aryl substrates, providing excellent results in terms of reaction time (less than one hour), yield (almost quantitative), amount of catalyst used (down to 5 mol‐%), and selectivity (polyfunctional substrates can be completely converted with no residual partially reacted products) . Reports on MW‐assisted reactions on alkyl halides have also appeared, showing that MW irradiation is also highly efficient for this class of substrates …”
Section: Metal Phosphonates Based On Tritopic Phosphonoaromatic LImentioning
confidence: 99%